Reduced Vascular Disease Mortality Associated with Improved 5‐Year Survival in an AD Cohort Followed for 25 years. (20th December 2022) - Pavlik, Valory N
Abstract: Background: It is important to monitor all‐cause and cause‐specific mortality in AD cohorts to assess impacts of new therapies and advances in management of co‐morbidities. Method: We compared all‐cause and cause‐specific morality in four cohorts of Alzheimer's disease (AD) patients ≥ 65 years old followed in an academic memory center from 1995‐2019. Patients' clinical and neuropsychological histories were obtained from an electronic data base. Vital status and cause of death through 2019 were ascertained using the National Death Index (NDI). Cohorts were defined based on enrollment date (1995‐1999, 2000‐2004, 2005‐2009, 2010‐2014). Hazard ratios (HRs) for five‐year all‐cause and cause‐specific mortality were compared across cohorts using Cox proportional hazards and competing risks regression, adjusting for age, sex, education, duration of symptoms at baseline, history of vascular disease, and baseline MMSE score. Result: 713 patients met selection criteria, and 686 deaths occurred within five years of baseline. Mean age at baseline was 78.7 ±6.5 and mean age at death was 82.2 ± 6.4 years. AD/Dementia accounted for proportionally more deaths over time: 39%, 46%, 55%, and 58% of deaths in Cohorts 1‐4 respectively. All‐cause mortality was significantly lower in Cohort 4 than in Cohorts 1‐3 (HR Cohort 2vs1 = .99±.10, p = .97; HR Cohort 3vs1 = .95±.09, p = .62; HR Cohort 4vs1 = .63±.07; p = . <001). There was a temporal trend toward reduced CVD mortality (HR Cohort 2vs1 = .69±.14; p = .06; HR Cohort 3vs1 = .67±.13; p = .04; HR Cohort 4vs1 = .40 ±.10; p = .001). Conclusion: The increasing proportion of AD deaths and increased survival in Cohort 4 is likely due to decreases in CVD mortality. The mortality experience of Cohort 4 can serve as a benchmark for future trends, particularly as new therapies are approved and impacts of the Sars‐CoV2 epidemic are observed.